1971
DOI: 10.1111/j.1365-2494.1971.tb00652.x
|View full text |Cite
|
Sign up to set email alerts
|

THE SIGNIFICANCE AND CONTROL OF POA TRIVIALIS IN RYEGRASS PASTURES

Abstract: A review of published information on the growth and productivity of Poa trivialis in relationship with perennial ryegrass is presented. The available evidence indicates that P. trivialis is usually outyielded by ryegrass, particularly under drought and infertile soil conditions. In addition, the quality and seasonal distribution of the yield is often of questionable value. It would therefore appear that P. trivialis can be considered an undesirable species in most intensively managed ryegrass pastures. Prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Susceptibility to winter frost has been recorded by Munro (1979). Allen (1966) gave a comprehensive review of rough meadow-grass while its significance in ryegrass pastures has been discussed by Haggar (1971). The latter commented that its DM production was usually lower than that of perennial ryegrass, particularly under sub-optimal growing conditions such as moisture stress; he also concluded that the presence of invasive rough meadow-grass could be considered undesirable in the most intensively managed ryegrass pastures.…”
Section: Rough Meadow-grassmentioning
confidence: 99%
“…Susceptibility to winter frost has been recorded by Munro (1979). Allen (1966) gave a comprehensive review of rough meadow-grass while its significance in ryegrass pastures has been discussed by Haggar (1971). The latter commented that its DM production was usually lower than that of perennial ryegrass, particularly under sub-optimal growing conditions such as moisture stress; he also concluded that the presence of invasive rough meadow-grass could be considered undesirable in the most intensively managed ryegrass pastures.…”
Section: Rough Meadow-grassmentioning
confidence: 99%
“…Despite significant differences among post‐herbicide treatments in relation to non‐target plant richness and diversity and target plant presence, no significant differences in production levels were observed. It is widely accepted that ryegrass‐dominated pastures are more productive, in terms of DM production, than their weed‐infested counterparts (Haggar, ), and weed control is often initiated if weeds constitute at least 20–30% of the sward (levels thought to impact on sward productivity and quality) (Oswald & Haggar, ). However, our results indicate that 20–30% weed infestation does not significantly alter production in permanent grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…It would therefore appear that weed grasses such as Poa spp. can be considered undesirable in most intensively managed sward pastures (Haggar, 1971).…”
Section: Introductionmentioning
confidence: 99%